1972
DOI: 10.1084/jem.135.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Basophilic Leukocytes in Allergic Contact Dermatitis

Abstract: A variety of cell-mediated hypersensitivity reactions in experimental animals include a prominent infiltrate of basophilic leukocytes. This form of reactivity has been designated cutaneous basophil hypersensitivity and is favored when sensitization to several types of antigen is accomplished without the use of complete Freund's adjuvant. A similar type of hypersensitivity response was sought in man using morphologic techniques which permit identification of basophilic leukocytes. Eight individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(108 citation statements)
references
References 12 publications
5
103
0
Order By: Relevance
“…The term PMD was introduced in the 1970s by Dvorak et al (1973Dvorak et al ( , 1974Dvorak et al ( , 1976, who first recognized a unique pattern of cell secretion in guinea pig and human basophils. Viewed by electron microscopy, basophils in PMD presented empty granule chambers that did not fuse with each other or with the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The term PMD was introduced in the 1970s by Dvorak et al (1973Dvorak et al ( , 1974Dvorak et al ( , 1976, who first recognized a unique pattern of cell secretion in guinea pig and human basophils. Viewed by electron microscopy, basophils in PMD presented empty granule chambers that did not fuse with each other or with the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils dominate helminth responses (1) and allergen late phase responses (6,32), whereas basophils dominate cutaneous basophil reactions (8,(11)(12)(13)(14)(15) and tick (3), as well as contact dermatitis responses (9,10). Differential basophil signaling via sequential and cooperatively acting chemokines could be a mechanism explaining these in vivo differences.…”
Section: Cooperation Of Chemokine Receptor Signalingmentioning
confidence: 99%
“…Although exceeded in numbers by eosinophils, basophils are a constituent of the cellular infiltrate in bronchial tissue of atopic asthmatic patients (4,5) and are further increased after allergen challenge (6). More prominently, basophils are a major constituent of the cellular infiltrate in the cutaneous late-phase reaction to allergens (6,7) and dominate some T cell-mediated delayed-type hypersensitivity responses, such as cutaneous basophil hypersensitivity (8), contact dermatitis (9,10), and late-phase IgG1- (11,12), IgE- (13), and other T cell-mediated responses (14,15).…”
Section: Basophil Responses To Chemokinesmentioning
confidence: 99%
“…Awadhiya et al (1982) also reported that the DTH reaction to DNCB in chickens consisted of infiltrated polymorphonuclear granulocytes and lymphocytes. In contrast, Dvorak and Mihm (1972) and Gershon et al (1975) reported that basophils comprise a significant portion of the inflammatory cells in almost all types of DTH reactions (DNFB, oxazolone, sheep red blood cells) in guinea pigs, humans and mice. The difference in type of granulocytes could be due to variation from one species to another.…”
Section: Discussionmentioning
confidence: 99%